P.093 Pulsatile tinnitus due to obstruction of transverse sinus by tentorial meningioma. (17th June 2016) - Maroun, FB; Avery, R; Lee, B; Bartlett, P; Hache, N
Abstract : Background: The etiology and treatment of pulsatile tinnitus is difficult and there are different causes for it. To our knowledge, an obstruction of the transverse sinus due to tentorial meningioma has not been reported.Methods: A 66 year old female presented a year ago with a sudden onset of a hissing sound in her ear which has persisted since. Neurologically she was intact. She was seen by otolaryngology who identified no cause for her tinnitus. A CT scan and MRI showed a tentorial meningioma on the right side with partial obstruction of the transverse sinus with evidence of partial chronic thrombus.Results: Removal of the meningioma with decompression of the transverse sinus resulted in immediate disappearance of the pulsatile tinnitus.Conclusions: This report can be added to the etiology of the difficult entity of pulsatile tinnitus particularly as it relates to its management.